Plotting the Profiles of Cartesian Surfaces by Ray-tracing - Yaseen, Nour Mohammed Hasan; Ahmed, Ahmed Kamal (Al-Nahrain Journal of Science, 2018)
A bundle of light rays, completely parallel to the optical axis, has been used to plot profiles of the Cartesian surfaces with constant paraxial curvature and varying asphericity factor. To accomplish this study, a programming code of skew ray tracing has been constructed to trace rays through all types of Cartesian or quadric surfaces of revolution. The results of this work show a remarkable utility of ray-tracing procedure to plot distinguished Cartesian surfaces profiles.